The Situation of Violence in the High Schools of Shkodra City. - Zamira Shabani; Irena Shala; Julian Kraja; Vera Gjinaj; Emiljano Pjetri (Albanian Journal of Trauma and Emergency Surgery, 2019)
Any behavior or attitude that harms the physical, emotional, and sexual well-being of one or more persons and affects the termination of the individual's normal development is considered as violence. Violence at school includes behaviors such as: victimization of a child and teachers, raping of a child and / or a teacher, physical and psychological harassment, cyber threatening, controversies, bullism, physical and psychological harm, teachers and students sexual violence, using of weapons in school environments. The main violence forms at school are: teachers to students, students to teachers, students to students.